Atypical Kawasaki Disease in a Two-Year-Old Girl with Initial Presentation of Acute Diarrhea - Desman Situmorang; Permata P Karina (Universitas Kristen Maranatha, 2021)
Kawasaki Disease is a spectrum of idiopathic, self-limited fever disease affecting childrenunder 5 years old. This disorder can be challenging to be diagnosed by a pediatrician since thereis no specific diagnostic laboratory test. One atypical Kawasaki Disease case presented withgastrointestinal symptoms, a two-year-old girl was hospitalized with fever, accompanied by non-hemorrhagic diarrhea three days before admission. Physical examination revealed unilateralcervical lymph enlargement and mild-moderate dehydration. Initial laboratory examinationresult showed thrombocytosis, leukocytosis (shift to the left), and normal routine fecal analysis.The patient was initially diagnosed with acute diarrhea with mild-moderate dehydration. She wastreated with a rehydration regimen and antibiotic, but her fever persisted. On the third day ofhospitalization, she fulfilled 3 of the classic Kawasaki Disease criteria (conjunctivitis, crackedlips with strawberry tongue, and lymphadenopathy). Further blood work resulted in increased C-reactive protein 43.35 mg/L and ESR 72 mm/hour, while chest X-ray and electrocardiographwere within normal limit. This patient was proceed to Hasan Sadikin General Hospital for furtherexamination and therapy. Atypical Kawasaki Disease can be a puzzling diagnosis due to itsuncommon presentations. Clinicians should importantly keep it in mind as a differential diagnosisin patients with prolonged fever. Keywords: atypical Kawasaki disease; diarrhea; prolonged fever